2019
DOI: 10.1161/strokeaha.118.023386
|View full text |Cite
|
Sign up to set email alerts
|

Association of Atrial Fibrillation With White Matter Disease

Abstract: Background and Purpose— Evidence suggests that atrial fibrillation (AF) is associated with increased risk of cognitive decline and dementia, even in the absence of stroke. White matter disease (WMD) is a potential mechanism linking AF to cognitive impairment. In this study, we explored the association between prevalent AF and WMD. Methods— We performed a cross-sectional analysis of participants attending the ARIC-NCS (Atherosclerosis Risk in Communities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…485 Although white matter disease had been raised as another potential driver, recent work appears to refute this. 482,486,487 Treatments that have been proposed to reduce the risk of cognitive impairment include risk factor management, 488 sinus rhythm maintenance with ablation, 489 and anticoagulation. [490][491][492] A modest effect has been observed with specific risk factor treatments, such as statins or angiotensin conversion enzyme inhibitor and angiotensin receptor blocker therapy in some studies, 481,488 but not in others.…”
Section: Cognitive Function/dementiamentioning
confidence: 99%
“…485 Although white matter disease had been raised as another potential driver, recent work appears to refute this. 482,486,487 Treatments that have been proposed to reduce the risk of cognitive impairment include risk factor management, 488 sinus rhythm maintenance with ablation, 489 and anticoagulation. [490][491][492] A modest effect has been observed with specific risk factor treatments, such as statins or angiotensin conversion enzyme inhibitor and angiotensin receptor blocker therapy in some studies, 481,488 but not in others.…”
Section: Cognitive Function/dementiamentioning
confidence: 99%
“…A previous report that examined clinically detected AF in relation to total WM FA reported no association. 26 Several studies have reported no association of AF with WMH volume 26 , 27 , 28 , 29 or with cortical and lobar microhemorrhages. 29 In the present study, greater spatial resolution and automated digital image analysis methodology may have offered greater precision in MRI measures and supplementing clinical AF with extended ambulatory monitoring more accurately classified AF.…”
Section: Discussionmentioning
confidence: 99%
“…Adverse effects of AF on cerebral small vessel disease may be one mechanism by which AF contributes to cognitive impairment. However, several studies failed to demonstrate an association between AF and WMHs [ 28 , 47 , 48 ]. Of note, a cross-sectional analysis of the community-based Framingham Heart Study did not report any associations between AF and lower total brain volume [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Incident AF is associated with structural changes in brain MRI, including worsened sulcal grade, larger ventricles, and subclinical cerebral infarctions. However, analyses from the ARIC and the Framingham Heart Study could not demonstrate any association between AF and WMHs or total brain volume after adjustment for vascular risk factors [ 39 , 47 , 49 ]. Notably, WMHs, attributed to small vessel disease and global cerebral hypoperfusion, were not associated with AF [ 49 ].…”
Section: Discussionmentioning
confidence: 99%